Sliding Mode Control untuk Mengatasi Nonlinearitas Gangguan pada Kendali Kecepatan Motor DC - Feriyonika (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
DC motor speed control is an example of plant where its feedback sensor is susceptible to noise. There are also some nonlinearities in DC motor due to changing in its internal components, white noise, driver problem, and direct external disturbances to controller signal. In this paper, Sliding Mode Control (SMC) was employed to overcome several disturbances in DC motor by localizing all states in sliding mode mechanism. Firstly, since internal components are unknown, system identification of DC motor was conducted to derive transfer function of the plant. The model was then used to design SMC by limiting amplitude of disturbances. To guarantee all states move to operating point (0,0), first order sliding surface equation and Lyapunov stability analysis were employed. The results showed that SMC could follow set point with no overshoot, rise time is 8.7 second, and error steady state is 0.009. Disturbances, represented by random signal (0.3, 0.5, and 1 times of maximum disturbance limit), were applied to check the robustness of the SMC. The result showed that SMC could still maintain the response around set point. Verification experiment was also conducted by adding disturbances which are out of maximum amplitude limit (3, 5, and 8 times of maximum amplitude limit). When 3 and 5 times of maximum amplitude limit disturbances were added, although there were oscillations, SMC could still maintain response around set point (marginally stable). It started to become unstable when 8 times of maximum amplitude limit disturbance was applied.